Health Insurance Model In The Perspective Of Health Economics: Transformation, Regulation, And Implementation In Indonesia - Ariska agustina; Prima Paramita Putri; Evi Kusumastuti Setianingrum; Budi Hartono; Alfani Ghutsa Daud (International Journal of Health and Pharmaceutical (IJHP), 2025)
Health insurance is an important component of the health financing system that aims to ensure equitable and sustainable access to health services. From a health economics perspective, the insurance system is able to mitigate the financial risk of illness while managing the efficiency and distribution of financing collectively. This study examines the development of health insurance models in Indonesia, ranging from traditional, modern, to managed care models, and analyses the challenges and implementation strategies of the National Health Insurance (JKN) programme by BPJS Kesehatan. A qualitative approach based on literature study was used with data sources from scientific journals, national regulations, BPJS Kesehatan reports, and public policy documents.The results show that the traditional model tends to be inefficient because it is prone to overutilisation and fraud. Modern models and managed care provide solutions through quality and cost control. However, the implementation of JKN in Indonesia still faces various challenges, such as delays in claim payments, moral hazard, and financing imbalances. One strategy for system sustainability is through the optimisation of participant fund assets, which can be productively invested to support promotive services, infrastructure, and strengthening the healthcare system. With transparent governance, the results of this asset optimisation can be returned for the benefit of the wider community. This study is expected to be a scientific contribution in supporting health financing policy reforms that are inclusive, efficient, and sustainable.